Diseño y caracterización de dispositivos plasmónicos - García Ortiz, César Eduardo (2013)
This thesis focuses on the design, fabrication and characterization of plasmonic devices. The studied structures include single and double plasmonic waveguide ring resonators, demultipleyors, and a plasmonic axicon. The structures were fabricated with electron-beam lithography and designed to operate in the near infra-red range. The study of surface plasmon polaritons in random arrays of nanoparticles is also included, as well as a description of a vectorial model for multiple scattering. The obtained experimental results match accurately with the numerical calculations for the different structures.